2017
DOI: 10.2337/dc16-1773
|View full text |Cite
|
Sign up to set email alerts
|

Nondiabetic Glucometabolic Status and Progression of Aortic Stiffness: The Whitehall II Study

Abstract: Structured Abstract Objective Aortic stiffness is an important predictor of future morbidity and mortality. Diabetes is associated with increased aortic stiffness, but the importance of non-diabetic glucometabolic status for accelerated aortic stiffening is unclear. We tested the hypothesis that adverse glucometabolic status is associated with accelerated aortic stiffening in non-diabetic individuals, independently of known risk factors for arterial stiffening. Research Design and Methods Glucometabolic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
3
15
0
2
Order By: Relevance
“…Change in insulin resistance may be minimal in the absence of weight change [35]; or obscured by the lack of standardization of insulin assays that hinder the comparison of assays over time [15]. However, a recent study has reported an association between an increase in long-term glucometabolic impairment and an increase in aortic stiffness associated with hemoglobin A1c and HOMA-IR [36]. Recent reports identified associations of aortic stiffness with dysregulation in various metabolic pathways in the setting of type 2 diabetes.…”
Section: Prospective Association: Insulin Resistance Index Since Midmentioning
confidence: 99%
“…Change in insulin resistance may be minimal in the absence of weight change [35]; or obscured by the lack of standardization of insulin assays that hinder the comparison of assays over time [15]. However, a recent study has reported an association between an increase in long-term glucometabolic impairment and an increase in aortic stiffness associated with hemoglobin A1c and HOMA-IR [36]. Recent reports identified associations of aortic stiffness with dysregulation in various metabolic pathways in the setting of type 2 diabetes.…”
Section: Prospective Association: Insulin Resistance Index Since Midmentioning
confidence: 99%
“…High aortic PWV has been shown, in two meta-analyses, to be associated with increased risk of CV events,14 15 independent of conventional risk factors of the FRS,15 with the caveat of study heterogeneity 16. In longitudinal studies, aortic PWV predicted CV mortality in the general population and in subjects with hypertension, diabetes mellitus (DM), glucose intolerance and chronic kidney disease 17–24. Nonpharmacological interventions, such as moderate-to-high exercise levels reduced progression of PWV compared with a sedentary lifestyle 25.…”
Section: Arterial Stiffness and Wave Reflectionsmentioning
confidence: 99%
“…Aortic stiffness, due to loss of elasticity of the artery wall, increases with age and risk factor exposure [4][5][6][7] is associated with higher systolic, pulse pressure and atherosclerosis [8], which are in turn important predictors of cardio-and cerebrovascular morbidity and mortality as well as predictors of cognitive decline [9]. The links between cardiovascular disorders and cognitive decline and dementia remain unclear.…”
Section: Introductionmentioning
confidence: 99%